Logistics systems for sustainable cities proceedings of the 3rd International Conference on City Logistics (Madeira, Portugal, 25-27 June, 2003) - Taniguchi, Eiichi; Thompson, Russell G. (Emerald, 2004)
Urban freight transport has become an important issue in urban planning. There are many challenges and problems relating to increasing levels of traffic congestion, environmental impacts and energy consumption. City logistics schemes are relatively new concepts that are aimed at increasing the efficiency of urban freight transport systems as well as reducing traffic congestion and impacts on the environment. However, new modelling, evaluation and planning techniques are required to conduct in-depth investigations before city logistics measures can be effectively deployed. This book, "Logistics Systems for Sustainable Cities", is an outcome of the Third International Conference on City Logistics (City Logistics III held in Madeira in 2003) organised by the Institute for City Logistics. It includes recent developments in the modelling, evaluation and planning of city logistics schemes. Since city logistics measures have already been implemented in several cities, a review of the performance of these innovative schemes is presented. As well, an overview of the visions for city logistics and public private partnerships for city logistics is given. A summary of the OECD report, Delivering the Goods 21st Century Challenges for Urban Goods Transport, is included. Recent developments in e-Commerce and e-Logistics are covered. The cover shows the beautiful Madeira Island, Portugal where the Third International Conference on City Logistics was held.
Keywords: Transportation -- General.; Business & Economics -- Industries -- Transportation.; Transport industries.; Economic systems & structures.; Freight and freightage -- Congresses.; Urban transportation -- Congresses.; Sustainable development -- Congresses.; elektronické knihy; electronic books